Application of Herbal Ingredients in Drinking Water Towards Productivity of Broiler Chicken - Mutia Rizkia Shaffira; D.D. Putri; Nurhayati Nurhayati (AIBPM Publisher, 2022)
This study aims to analyze the effect of using red ginger and brotowali either singly or in combination as herbal ingredients used in drinking water on broiler chicken productivity. This research was conducted at the Lampung State Polytechnic using a Completely Randomized Design (CRD) with 4 treatments and 5 replications and each replication consisted of 5 broiler chickens. The treatments consisted of: P0 = drinking water without the addition of red ginger and brotowali extract (control), P1 = drinking water + 1% red ginger extract, P2 = drinking water + 5.12 ml/kgbw of brotowali extract, P3 = drinking water + combination of red ginger extract and brotowali. The variables observed included ration consumption, body weight gain, ration conversion and mortality. The results showed that the addition of red ginger and brotowali extracts in drinking water, either singly or in combination, had a significant effect (P<0.05) on body weight gain, ration conversion and mortality, but had no significant effect on ration consumption. The conclusion of this study is that the application of herbal ingredients in drinking water can improve the productivity of broiler chickens.Â Keywords: broiler, red ginger extract, brotowali extract, productivity.